Evaluation of cultivated and wild genotypes of Lens species under alkalinity stress and their molecular collocation using microsatellite markers. - Dharmendra Singh; Chandan Kumar Singh; Yash Pal Singh; Vijayata Singh; Rajendra Singh; Ram Sewak Singh Tomar; Satish Kumar Sanwal; Sourabh Karwa; Vinay Kumar Mishra; Susheel Kumar Sarkar; Madan Pal; Arun Kumar; et al. (PLoS ONE, 2018)
In this study, 285 lentil genotypes were phenotyped under hydroponic and alkaline field conditions. Significant genotypic variation for alkalinity stress was observed among the six Lens species screened hydroponically and in the field having pH up to 9.1. The crucial parameters, like whole Na+ and K+ contents and the Na+/K+ ratio at 40 mM NaHCO3 were found significantly correlated with seedling survivability under hydroponics (r = -0.95, r = 0.93 and -0.97). Genotypes, ranked on the bases of seed yield, restricted uptake of Na+ with thick pith area, increased vascular bundles, less H2O2 production and low Na+/K+ ratio, were found important physio-anatomical traits for alkalinity stress tolerance. The proper regulation of Na+ uptake was found for maintaining higher K+. This relationship is probably the main factor responsible for a better mechanism for tolerance to high pH up to 9.1 in tolerant breeding lines PDL-1 and PSL-9 (cultivars) and ILWL-15, ILWL-192 and ILWL-20 (wild accessions). Based on UPGMA dendrogram, all the genotypes were clustered into four diverse groups. DMRT was implied within the group to differentiate genotypes based on phenotypic response under alkalinity stress. These results can be utilized for selecting diverse parents for developing alkalinity tolerant genotypes.